2013
DOI: 10.1016/j.image.2013.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Full-reference quality assessment of stereopairs accounting for rivalry

Abstract: We develop a framework for assessing the quality of stereoscopic images that have been afflicted by possibly asymmetric distortions. An intermediate image is generated which when viewed stereoscopically is designed to have a perceived quality close to that of the cyclopean image. We hypothesize that performing stereoscopic QA on the intermediate image yields higher correlations with human subjective judgments. The experimental results confirm the hypothesis and show that the proposed framework significantly ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
236
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 314 publications
(250 citation statements)
references
References 46 publications
1
236
0
1
Order By: Relevance
“…Binocular vision contains a large amount of information, so it is necessary to map the common information in an image which can reflect left image and right image. The appearance of the cyclopean map has solved this problem [19,20].…”
Section: Binocular Visionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binocular vision contains a large amount of information, so it is necessary to map the common information in an image which can reflect left image and right image. The appearance of the cyclopean map has solved this problem [19,20].…”
Section: Binocular Visionmentioning
confidence: 99%
“…At present, there are a lot of researches on the objective evaluation of stereo image quality [17][18][19] . Some papers construct the models of human visual system (HVS), which can evaluate the quality of the stereoscopic image [43].…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that Q3D-RBM performs comparably with FF QA metrics, while it is a RR 3D QA metric, independent of distortions type. The second experiment was done on the Phase II of the LIVE 3D Image Quality Database [12,24]. This contains 8 reference images with 45 distorted images for each reference one.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Both layers are superimposed by a layer of hidden neurons, using three way multiplicative interactions. We tested our approach on two benchmark databases, which include both, 3D images and subjective QoE results [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Towards filling these gaps, we begin by studying the performance differences of S3D discomfort prediction models using three nominal disparity algorithms having different levels of complexity. We then introduce two new sets of discomfort predictive features, the uncertainty map and natural scene statistics, which have previously found use in 3D image quality assessment models [20][21][22]. These features efficiently improve the performance of prediction models that use low complexity disparity calculation methods.…”
Section: Introductionmentioning
confidence: 99%